Characterization of a commercial scintillation detector for 2-D dosimetry in scanned proton and carbon ion beams. (February 2017) - Russo, S.; Mirandola, A.; Molinelli, S.; Mastella, E.; Vai, A.; Magro, G.; Mairani, A.; Boi, D.; Donetti, M.; Ciocca, M.
Highlights: A systematic characterization of Lynx® for proton and carbon ion beams is presented. Single spot and scanned beam characterization results against EBT3 films are shown. Real time analysis allows time sparing in daily quality assurance procedures. Abstract: Introduction: Pencil beam scanning technique used at CNAO requires beam characteristics to be carefully assessed and periodically checked to guarantee patient safety. This study aimed at characterizing the Lynx® detector (IBA Dosimetry) for commissioning and periodic quality assurance (QA) for proton and carbon ion beams, as compared to EBT3 films, currently used for QA checks. Methods and materials: The Lynx® is a 2-D high-resolution dosimetry system consisting of a scintillating screen coupled with a CCD camera, in a compact light-tight box. The scintillator was preliminarily characterized in terms of short-term stability, linearity with number of particles, image quality and response dependence on iris setting and beam current; Lynx® was then systematically tested against EBT3 films. The detector response dependence on radiation LET was also assessed. Results: Preliminary results have shown that Lynx is suitable to be used for commissioning and QA checks for proton and carbon ion scanning beams; the cross-check with EBT3 films showed a good agreement between the two detectors, for both single spot and scanned field measurements. The strong LET dependence of the scintillator due to quenching effect makes Lynx® suitable only for relative 2-D dosimetry measurements. Conclusion: Lynx® appears as a promising tool for commissioning and periodic QA checks for both protons and carbon ion beams. This detector can be used as an alternative of EBT3 films, allowing real-time measurements and analysis, with a significant time sparing.